Problematika Masyarakat Lokal Dalam Pengembangan Desa Wisata Bayung Gede, Kecamatan Kintamani, Kabupaten Bangli - Pujiwiyasnawa, I Made; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA, 2019)
This research aims to find out the problems of local community of Bayung Gede to develop tourism Village. Research technique as qualitative method to find, describe and understanding focus of this research. With purpossive sampling as the specific informant and technique analysis data used descriptive qualitative. The result of this research show a complex problems when local community of Bayung Gede develop their own tourism village.  The problems are garbage, infrastructure maintenance, vision and mission tourism village equalizing, souvenir core product and marketing icons. However, as long few years this tourism village has been succeed to done tourism activity with not forced participation or spontal typical participate. Keywords: Problems, Participation, Tourism Village.